Odontometric analysis of molars for sex determination - Larissa Chaves Cardoso Fernandes; Carolina Vieira Lucena Veloso; Julyana de Araújo Oliveira; Paloma Rodrigues Genu; Bianca Marques Santiago; Patrícia Moreira Rabello (Universidade Estadual de Campinas, 2016)
Aim: To investigate the existence of sexual dimorphism between the first and second permanent molars. Methods: A cross-sectional, observational, blind study using comparative and statistical descriptive procedures. The sample included 50 pairs of plaster casts from undergraduate dental students (25 men/25 women) from the Federal University of Paraíba, João Pessoa/PB, Brazil, aged 20-26 years. Odontometric measurements of first and second maxillary/mandibular, right/left permanent molars were performed. Mesiodistal (MD) and buccolingual/palatal (BL/BP) widths and the distance between the lingual cusps of corresponding molars in opposite quadrants, were measured. The data were analyzed by Student's t test and ANOVA with Bonferroni (p≤0.05). Results: The crowns of all first molars were statistically larger in men than in women (p<0.05). Maxillary and mandibular left second molars (#27 and #37) did not differ in their MD widths (p=0.66, p=0.75), whereas mandibular left and right second molars (#37 and #47) showed statistically different BL widths (p=0.007 and p=0.008). As to the distance between the lingual cusps, only the first left-to-right mandibular molars (#36-46) showed no sex dimorphism (p=0.107). Conclusions: Molars are larger in males than in females. Individually, first molars demonstrated higher evidence of sex distinction than second molars.